Scalpelus loofi gen. n., sp. n. (Nematoda : Dorylaimida) from Costa Rica (Journal of Nematode Morphology and Systematics, 2009)
Scalpelus loofi gen. n., sp. n. is described and illustrated from natural forest in Costa Rica. The new genus is characterized by having continuous lip region with amalgamated lips, outer and inner labial papillae close to each other, wine-glass-shaped amphid, wide asymmetrical scalpel-like odontostyle, rod-like odontophore, S2N well developed and far from base, amphidelphic female genital system, and short hemispheroid tail.